FORMAT HISTORIOGRAFI ISLAM NUSANTARA - Salman Salman; Lukmanul Hakim (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2019)
The problem in this paper is how the historiography format of the Nusantara Islam. Whereas the focus of his study of the traditional historiography of Nusantara Islam, the historiography of the archipelago's Islam and the historiographic themes of the archipelago's Islam. The approach used in this study is the historiography and analytical descriptive approach. Islamic historiography of the archipelago can be divided into two. First, the traditional historiography of the Islamic archipelago. Second, the modern historiography of Islamic Nusantara. The Islamic historiography of the archipelago can be grouped into five. First, saga. Second, khabar. Third, Tambo. Fourth, story. Fifth, genealogy. The historiographic themes of Nusantara Islam can be divided into five. First, the theme revolves around the work of local history writing. Second, the theme revolves around the work of general history writing. Third, the theme revolves around the work of writing military history. Fourth, the theme revolves around the work of biographical writing. Fifth, the theme revolves around the work of historical novels.